Manual for Developing a Student Intern Program in Politics and Government An Adopter's Guide Referenced in "Promising Practices in Oregon Education," 1974 - Oregon State Dept. of Education, Salem; Svicarovich, John; Oregon State Dept. of Education, Salem ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The manual describes an offcampus intern program for 12th-grade students in political science. Description of the project, Government Responsibility and Student Participation (GRASP), is divided into six chapters. Chapter I, Deciding Whether to Adopt the Model, identifies the need for an intern course and projects presumed student accomplishments upon completion of the course. Chapter II, Determining Program Feasibility, identifies potential financial resources and determines organizational accountability. Chapter III, Planning Program Operation, defines management, personnel, and school responsibilities, and it indicates management objectives. Chapter IV, Founding the Program, discusses recruiting government agencies and securing commitment for support and participation. Chapter V, Implementing the Program, describes selection and orientation of staff and students, discusses placement of students in government agencies, and delineates instructional guidelines. Chapter VI, Evaluating the Program, identifies six general indices for measuring the impact of the internship experience. Included are tests, questionnaires, evaluation forms, and a bibliography. (Author/DB)
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Innovation; Educational Objectives; Evaluation; Experimental Programs; Government Role; Guides; Internship Programs; Political Science; Practicums; Program Descriptions; Program Design; Program Development; Relevance (Education); School Community Relationship; Secondary Education; Student Needs; Student Participation; Teaching Methods; United States Government (Course); Work Experience Programs; Guides, General